Clinical approaches associated with the initial care of multiple trauma patients: Literature review (Research, Society and Development, 2021)
Initial care for trauma victims requires agility and skill through a highly trained team, where the approach is effective, reducing the risks of a possible evolution to the patient's death. The present study aimed to evaluate current concepts related to clinical approaches associated with the initial care of polytrauma patients. An integrative literature review of the literature was carried out in order to synthesize the knowledge pertaining to the theme. The research was carried out in the databases of Pubmed and CAPES Periodicals between the years 2003 and 2019, having as descriptors: “Trauma”, “mortality” and “polytrauma”. Sixteen scientific productions that met the inclusion criteria and were selected. The region of the face, for presenting a prominent anatomy, with great exposure and little protection, ends up being the most affected area, being responsible for 35 to 45% of the involvement in patients. The ATLS (Advanced Trauma Life of Support) system aims to outline and standardize the initial approach to polytrauma patients. Therefore, an agile and effective care for polytrauma patients is essential for the diagnosis and treatment of the patient to be successful.